First report of the Horse nettle virus infecting tomato (Solanum lycopersicum L.) in the United States - Jindal, Salil (Plant disease, 2024)
Tomato (Solanum lycopersicum L.), a member of the Solanaceae family, represents one of the most extensively cultivated vegetable species worldwide and traces its origin to western South America (Caruso et al. 2022). In a field survey conducted in 2023 in Bixby, Tulsa County, Oklahoma, distinct symptoms were noted in two plants: one exhibited mottling and cupping of leaves and brown discoloration on leaves, petioles, and stems, while the other displayed a downward curling of leaves. Leaf samples from both symptomatic tomato plants (labelled as K4 and K5) were collected, and total RNA was extracted individually via the TRI Reagent® method (Molecular Research Center Inc., Cincinnati, OH, USA). Subsequently, the RNA samples were pooled and subjected to high-throughput sequencing (HTS) on the NextSeq 500/550 high-output kit v2.5 (Illumina, U.S.A.) at the genomic facility, Oklahoma State University (Stillwater, OK). Total read count of 8,227,020 (average length =150.5 bp) was obtained, trimmed, and de novo assembled using CLC Genomics Workbench v22.0.1 (QIAGEN) and used for BLASTn and BLASTx analysis. Two contigs: 6,375 bp (average coverage 2,915.92, read count 142,538) and 3,564 bp (average coverage 3,035.91, read count 82,370) from the pooled sample showed 88.6% and 96.7% nucleotide identities with RNA 1 (OP292294) and RNA 2 (OP292295) of Horse nettle virus A (HNA-A) isolate MD-1, respectively. Sequences of both partial contigs (RNA 1, accession no. PP063196) and RNA 2, accession no. PP063197) were submitted to GenBank. The HTS data did not reveal any other viral or viroid sequences in these two tomato samples. To further confirm the presence of HNV-A, total RNA from K4 and K5 samples was tested individually by RT-PCR using HNV specific primers (Supplementary Table 1) based on the two partial contig sequences. The expected PCR products (491 bp and 451 bp) were obtained only from the K4 sample and none from the K5 sample. PCR products were extracted from an agarose gel, cloned into the pGEM®-T Easy vector (Promega), and transformed into Escherichia coli DH5α cells (New England Bio Labs). Two clones for each PCR product were sequenced by Sanger sequencing. Nucleotide sequence comparisons and BLASTn analysis of 491 bp and 451 bp showed 86% and 97% nucleotide identity with RNA 1 and RNA 2 of HNV-A isolate MD-1 (OP292294 and OP292295), respectively. Additionally, eight more leaf samples from eight different symptomatic tomato plants were collected in the same field and tested by RT-PCR as described above. All eight samples were positive by RT-PCR, but no PCR band was obtained in the total RNA from a healthy tomato leaf used as a control. Sequences from the PCR products were identical to the obtained HTS sequences. Our results confirmed for the first time that HNV-A can infect tomatoes. Currently, HNV-A has been reported to only infect a single weed (Horse nettle, Solanum carolinense) (Zhou et al. 2023). The identification of HNV-A in tomatoes in Oklahoma suggests a potential host shift is of concern for local growers as well as tomato growers worldwide. This shift underscores the urgency for an in-depth investigation into the transmission and host specificity of HNV-A. This is the first report in the United States and the world that HNV-A could infect tomatoes naturally in a grower field